Automation of Solubility Measurements on a Robotic Platform. Issue 6 (4th March 2016) - Thygs, Fabian B.; Merz, Juliane; Schembecker, Gerhard
Abstract: Experimental investigation in the laboratory can be accelerated and supported by miniaturized automation techniques. In the design of unit operations, e.g., for crystallization and precipitation processes or for chromatographic separations where no solids should appear during the run, reliable solubility data are mandatory. The development and validation of a robotic routine for completely automated solubility measurements are introduced. The triple‐determination of automated solubility measurements of the model systems succinic acid and adipic acid/water have a relative standard deviation below 0.99 % and are comparable to literature and manual experiments. Data are generated with high precision and accuracy, and the experimental effort and the hands‐on time are reduced significantly to a few minutes necessary to prepare the platform since all subsequent pipetting and control steps are automated. Abstract : The integration of automated platforms into daily routine work in laboratories is an effective way to accelerate and support experimental investigation. A completely automated method for the measurement of compound solubility on a custom‐built automated platform is developed which works without any manual intervention. Data are generated with high precision and accuracy.